The association between caffeine intake and risk of kidney stones: A population-based study - Geng, Jiwen; Qiu, Yuxuan; Kang, Zhefeng; Li, Yupei; Li, Jiameng; Liao, Ruoxi; Qin, Zheng; Yang, Qinbo; Su, Baihai (Frontiers in Nutrition, 2022)
Background: Although many studies have proven the beneficial effects of caffeine on human health, the association between caffeine intake and the risk of kidney stones is limited in large epidemiologic studies. Objectives：We aimed to investigate the association between caffeine intake and the risk of kidney stones. Methods: A total of 30,716 participants (with a weight number of 204,189,886) with a history of kidney stone were included in this analysis. All data were survey-weighted, and corresponding logistic regression models were performed to examine the associations between caffeine intake and the risk of kidney stones. Results: In a fully adjusted model, a per-quartile increase in caffeine intake was associated with a 5.32% decreased risk of kidney stones. In the subgroup analysis, the multivariate-adjusted odds ratios (95% confidence intervals) of the risk of kidney stones for per-quartile increments in caffeine intake were 0.9650 (0.9643,0.9656) for men, 0.9320 (0.9313,0.9327) for women, 0.9384 (0.9378,0.9389) for white race individuals, 1.0281 (1.0270,1.0292) for nonwhite race individuals, 0.9460 (0.9455,0.9465) for overweight/obese individuals, 0.9314 (0.9303,0.9324) for non-overweight individuals, 0.9100 (0.9094,0.9105) for caffeine from coffee, and 1.0021 (1.0013,1.0029) for caffeine from noncoffee sources. Conclusion: Caffeine intake was negatively associated with the risk of kidney stones. In subgroup analyses, the negative association of caffeine with kidney stone risk was only found in white individuals. In addition, the decreased risk was found higher in women and non-overweight individuals. especially for women, white individuals and nonoverweight individuals. The protective effect of caffeine intake from coffee on stone formation was more significant than that of caffeine from noncoffee sources.